2018
DOI: 10.1002/acr.23292
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Antinuclear Antibodies for Classifying Systemic Lupus Erythematosus: A Systematic Literature Review and Meta‐Regression of Diagnostic Data

Abstract: The results of this systematic literature review and meta-regression confirm that IIF-ANAs have high sensitivity for SLE. ANAs at a titer of 1:80 have sufficiently high sensitivity to be considered as an entry criterion for SLE classification criteria, i.e., formally test other classification criteria for SLE only if ANAs of at least 1:80 have been found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
1
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 147 publications
(113 citation statements)
references
References 91 publications
5
95
1
12
Order By: Relevance
“…A systematic review of Medline, Embase, and the Cochrane database identified 13,080 patients from 64 studies reporting ANA by immunofluorescence on HEp‐2 cells. Meta‐regression of the operating characteristics of ANA found a sensitivity of 97.8% (95% CI 96.8–98.5%) for ANA of ≥1:80, supporting use of ANA as an entry criterion . Since some SLE centers do not have access to HEp‐2 ANA, and in view of ongoing work on the standardization of serology and potential future advances in the field, the steering committee and additional autoantibody consultants (MJF and PLM) recommended the provision “or an equivalent positive ANA test.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review of Medline, Embase, and the Cochrane database identified 13,080 patients from 64 studies reporting ANA by immunofluorescence on HEp‐2 cells. Meta‐regression of the operating characteristics of ANA found a sensitivity of 97.8% (95% CI 96.8–98.5%) for ANA of ≥1:80, supporting use of ANA as an entry criterion . Since some SLE centers do not have access to HEp‐2 ANA, and in view of ongoing work on the standardization of serology and potential future advances in the field, the steering committee and additional autoantibody consultants (MJF and PLM) recommended the provision “or an equivalent positive ANA test.…”
Section: Resultsmentioning
confidence: 99%
“…During the phase I Delphi exercise, 58% of SLE experts did not feel comfortable and an additional 19% were uncertain about classifying a patient with SLE in the absence of ever having a positive ANA . The systematic literature review and meta‐regression of data on 13,080 subjects demonstrated ANA ≥1:80 to have a sensitivity of 98% with a lower limit of the 95% CI at 97% . In the phase I early SLE cohort, 99.5% of the 389 SLE patients were ANA positive .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical history and blood tests did not reveal signs of a small vessel vasculitis due to a rheumatic disease. Sporadic case reports of PXE associated with systemic lupus erythematodes seem unlikely due to negative titer of antinuclear antibodies (ANA) [11]. Therefore, a microvascular manifestation of PXE may be responsible for the decrease of AB-Indices following exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all SLE patients exhibit ANA at diagnosis, with a 1:80 immunofluorescent titer showing up to 98% sensitivity but 75% specificity for SLE classification. 16 ANA are also found in individuals with many other autoimmune diseases, malignancies, hepatic diseases, unaffected family members of lupus patients, and even up to 14% of healthy individuals, 17 especially with increasing age. Therefore, a positive ANA serves as a necessary but insufficient criterion for SLE classification or diagnosis, but not as a definitive test.…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%